The impact of government debt on foreign direct investment in Zambia - Mwape, Isaac (Faculty of Commerce, 2023)
Zambia is a developing nation that seeks economic growth through gross domestic product (GDP) growth, among other economic drivers. Between the years 2011 and 2020, Zambia embarked on an infrastructure development programme, mainly through construction of roads and airports. To do these projects, Zambia borrowed heavily on one hand while promoting the nation as an attractive destination for foreign direct investment (FDI) inflows on the other hand. The study sought to answer the question, can a country that is highly indebted attract meaningful FDI inflows that would spur economic growth? The research looked at a period of ten (10) years from 2010 to 2020 and analysed publicly available data to form the basis for the findings and recommendations. The research findings show that there is negative, however insignificant relationship between government debt and foreign direct investment. In addition, the findings also show that there is a positive relationship between inflation and FDI. This relationship is significant however, in contrast with a prior expectation. Moreover, a significant negative relationship between interest rate and investment was also established whilst a negative, however insignificant relationship was established between exchange rate and FDI. The implications of the recommended policy issues will only yield the desired results when implemented in an integrated manner as opposed to an exclusive approach. The government debt needs to reduce in order to make the country more attractive to foreign direct investors. Policy also needs to be formulated that should target an inflation rate that contributes to the attraction of a positive net foreign direct invest inflows. Interest rate and foreign exchange rate policies that attract investment will also need to be put in place in order to attract investments that will spur development.